Prevalence and factors associated with preoperative parental anxiety among parents of children undergoing anesthesia and surgery: A cross-sectional study. (2020) - Ayenew, Netsanet Temesgen; Endalew, Nigussie Simeneh; Agegnehu, Abatneh Feleke; Bizuneh, Yosef Belay
Abstract: Introduction: Parents experience anxiety and concern about their children's anesthesia and surgeries, which may affect their ability to function normally and the operating staff caring for the child. We aimed to assess the prevalence and factors associated with parental anxiety. Methods: Institutional-based cross-sectional study was conducted from the 1st February to May 30th, 2019. 203 parents of children were enrolled in the study. The level of anxiety was measured using the State and Trait Anxiety Inventory (STAI). Results: Overall prevalence of parental anxiety was 74.2%. Being mother (AOR = 4.45, 95% CI = 1.76–11.27), not informed about anesthesia (AOR = 7.02, 95% CI = 2.62–18.80), child age < 1 year (AOR = 4.10, 95% CI = 1.25–19.15), being farmer (AOR = 9.73, 95% CI = 1.86–50.76), living in rural area (AOR = 4.50, 95% CI = 1.31–15.42), and fear of post-operative pain of the child (AOR = 6.63, 95% CI = 2.42–18.18) were significantly associated with parental anxiety. Conclusion: Prevalence of preoperative parental anxiety was high in our setup. Age of child, parent's gender, information about the anesthesia, fear of post-operative pain, and parent's occupation were associated predictor factors. The operating staff should consider these factors when interacting in the perioperative periods of their child's anesthesia and surgery. Highlights: The prevalence of parental anxiety was high. Parents of younger age children, female parents, limited information and fear of post-op pain more linked to Pre-op anxiety. The operating staff should consider parents' anxiety during the perioperative period.